2010
DOI: 10.1089/aid.2009.0308
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Inadequate Vitamin D Exacerbates Parathyroid Hormone Elevations in Tenofovir Users

Abstract: Parathyroid hormone (PTH) elevations are associated with reduced bone mineral density and adverse health outcomes and have been reported in patients with HIV infection. We aimed to examine the impact of vitamin D status and tenofovir (TDF) use on PTH levels among HIV-infected patients receiving combination antiretroviral therapy (cART). Demographics, medication and supplement use, and clinical data, including 25-hydroxyvitamin D [25(OH)D] and PTH, were collected on 45 HIV-infected men on ART. Suboptimal vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 14 publications
4
30
2
Order By: Relevance
“…TDFassociated bone changes may occur through a TDF effect on parathyroid hormone (16,20), as parathyroid hormone secretion increases soon after initiating TDF (21). Vitamin D deficiency (22) may exacerbate this increase in parathyroid hormone (20,23), but TDF-associated increased parathyroid hormone is found even in persons with sufficient vitamin D (24). Short-term vitamin D supplementation reduces TDF-associated increased parathyroid hormone but does not ameliorate TDF-associated phosphate loss (24,25).…”
mentioning
confidence: 99%
“…TDFassociated bone changes may occur through a TDF effect on parathyroid hormone (16,20), as parathyroid hormone secretion increases soon after initiating TDF (21). Vitamin D deficiency (22) may exacerbate this increase in parathyroid hormone (20,23), but TDF-associated increased parathyroid hormone is found even in persons with sufficient vitamin D (24). Short-term vitamin D supplementation reduces TDF-associated increased parathyroid hormone but does not ameliorate TDF-associated phosphate loss (24,25).…”
mentioning
confidence: 99%
“…42,60 In some studies designed for the purpose, PTH concentration or prevalence of sHPTH was found to be consistently associated with 25OHD level and/or ART therapy (PIs and NNRTIs). 7,34,36,[39][40][41][42]45,51 Three articles, in particular, found a correlation between tenofovir use and higher parathyroid hormone concentrations. 7,36,39 In addition, Masia et al evaluated changes in PTH after the initiation of two different ART regimens.…”
Section: Secondary Hyperparathyroidism and Parathyroid Hormone Statusmentioning
confidence: 99%
“…7,34,36,[39][40][41][42]45,51 Three articles, in particular, found a correlation between tenofovir use and higher parathyroid hormone concentrations. 7,36,39 In addition, Masia et al evaluated changes in PTH after the initiation of two different ART regimens. 7 Both regimens produced significant increases in PTH concentration, and in the proportion of patients presenting with sHPTH during the follow-up period.…”
Section: Secondary Hyperparathyroidism and Parathyroid Hormone Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…9 However, elevated serum concentrations of PTH were more profound in patients with vitamin D (VitD) deficiency. 10,11,12 Tenofovir disoproxil fumarate undergoes initial di-ester hydrolysis in plasma to tenofovir (TFV). A proposed bone loss mechanism associated with TFV, a phosphonate, is selective uptake by osteoclasts via a mechanism similar to that of bisphosphonates, which eventually cause cellular stress.…”
Section: Introductionmentioning
confidence: 99%